Cluster analysis for test-retest Reliability (2010)
Conventional statistical model for assessing test-retest reliability of questionnaire is to compare composite scores of matched subtests or items between periods. Current study examined test-retest reliability in terms of both subtest and item wise comparison through paired t-test statistics. Data were collected from 72 students twice within 8 months intervals using reading motivation questionnaire (Dutta Roy, 2003). The questionnaire includes 3 intrinsic (rApp, rKnow,rAch) and 4 extrinsic (rAes, rRecog, rAff and rHarm) reading motivation subtests. Finding inconsistency between both subtest and item wise comparison, I propose a model of clustering items between periods. Hierarchical clustering with complete linkage shows that more than 55% of both test and retest items are assembled in the primary cluster suggesting high test retest reliability among 6 reading motivation variables.